A lithium-ion battery stainless steel raw material inspection device and inspection method
By designing a test device for raw materials of stainless steel of lithium-ion batteries, and using the timing current method to test the change of current value, the problem of difficult to quickly detect the corrosion resistance of raw materials of stainless steel of lithium-ion batteries to electrolyte in the prior art is solved, and the corrosion resistance of raw materials of stainless steel of lithium-ion batteries to electrolyte is realized. Fast and accurate detection results.
Patent Information
- Application Number
- CN202110170053.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-02-08
AI Technical Summary
The prior art is difficult to quickly and accurately detect the corrosion resistance of raw materials for lithium-ion batteries to electrolytes, resulting in the problems of short circuits and performance degradation in batteries during long-term use.
Design a stainless steel raw material inspection device for lithium-ion battery. By placing the device in an electrochemical workstation for timing current testing, observing the change of current value over time, we can judge whether the stainless steel raw material sheet has corrosion, so as to quickly detect it and the electrolyte. adaptability between.
It realizes rapid and intuitive judgment of the adaptability between the raw materials of stainless steel of lithium-ion batteries and the electrolyte, avoids the problems of long time periods and complex operations in traditional methods, and improves detection efficiency and accuracy.
Smart Images

Figure CN112683980B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of batteries, in particular to a device and method for inspecting stainless steel raw materials for lithium-ion batteries. Background Art
[0002] Different types of electrolytes have different corrosive effects on different types of stainless steel, which causes the corrosion of the battery steel shell by the electrolyte to accelerate after long-term storage due to the influence of external temperature and battery voltage, thus causing a short circuit inside the battery. Therefore, the degree of corrosion of different types of stainless steel in different types of electrolytes will seriously affect the performance of the battery. The battery will fail during long-term use, giving customers a very bad experience. At the same time, for manufacturing companies, this is undoubtedly the biggest loss.
[0003] The selection of electrolyte type and stainless steel shell for different battery models is crucial. When faced with how to match batteries with different types of stainless steel, most companies will choose the stainless steel type of the battery shell based on the recommendations of stainless steel manufacturers and conventional experience. However, once the selected stainless steel type does not match the electrolyte, it will cause irreparable losses. Some battery manufacturers will first make a complete battery, then store the complete battery for a long time (30 days) at a specific temperature environment (normal temperature or 45°C), and then test whether the battery voltage drops significantly or dissect the battery to check its internal corrosion, so as to determine the compatibility between the electrolyte and the battery steel shell. However, the time period is too long, and it is impossible to make corresponding changes quickly in line with market changes during the development of new products.
[0004] In addition, there is also a "method for determining the corrosion rate of metals by means of the Tafel curve (also called "Tafel curve")" in the prior art. Specifically, the method comprises the following steps: pouring the electrolyte into the electrolytic cell, and then placing the steel sheet to be tested as the working electrode, saturated calomel as the reference electrode, and platinum as the counter electrode to form a three-electrode based Tafel detection electrochemical system. However, it is difficult to achieve absolute sealing of the electrolytic cell of the electrochemical system of this method, and for lithium-ion batteries, the water content of the electrolyte is generally required to be below 50ppm. Therefore, the existing Tafel detection electrochemical system is not suitable for testing lithium-ion battery electrolytes. Moreover, the existing Tafel detection electrochemical system is a three-electrode system with a complex system structure and inconvenient operation. At the same time, when the Tafel detection electrochemical system is tested on an electrochemical workstation, parameter settings are also required, which is complex to operate.
[0005] Therefore, it is of great significance to develop a device and method that can quickly detect the corrosion resistance of stainless steel raw materials of different types of lithium-ion batteries to electrolytes. Summary of the invention
[0006] One of the purposes of the present invention is to provide a lithium-ion battery stainless steel raw material inspection device. By placing the device on an electrochemical workstation to perform a "potential step chronocoulometry (also known as "chronoamperometry")" test, it is possible to determine whether corrosion occurs to a stainless steel raw material sheet in the inspection device based on whether the current value in the test result fluctuates over time, thereby achieving rapid detection of the compatibility between the stainless steel raw material sheet in the inspection device and the electrolyte.
[0007] A lithium-ion battery stainless steel raw material inspection device comprises a sealed shell, the sealed shell is composed of a positive electrode shell, a negative electrode shell and a sealing ring, wherein the positive electrode shell and the negative electrode shell are both cylindrical, the positive electrode shell is only open at the lower end, and the negative electrode shell is only open at the upper end, the positive and negative electrode shells are buckled up and down, and a gap is left between the positive and negative electrode shells, and the sealing ring is filled in the gap to achieve sealing and insulation between the positive and negative electrode shells; a metal lithium sheet, a diaphragm and a lithium-ion battery stainless steel raw material sheet to be tested are stacked in sequence from bottom to top in the sealed shell; the diaphragm completely covers the metal lithium sheet and the lithium-ion battery stainless steel raw material sheet, so that the diaphragm can The metal lithium sheet is completely separated from the stainless steel raw material sheet of the lithium-ion battery; the upper surface of the stainless steel raw material sheet of the lithium-ion battery is in contact and electrically connected with the inner bottom surface of the positive electrode shell, and the lower surface of the metal lithium sheet is in contact and electrically connected with the inner bottom surface of the negative electrode shell; the inner cavity of the cylinder of the sealed shell is encapsulated with an electrolyte for the lithium-ion battery to be tested, and the stainless steel raw material sheet of the lithium-ion battery, the diaphragm and the metal lithium sheet are all immersed in the electrolyte; the positive and negative electrode shells are both made of the same material as the stainless steel raw material sheet of the lithium-ion battery; when working, the inspection device is placed in an electrochemical workstation and the chronoamperometry program of the electrochemical workstation is started for detection.
[0008] Chronoamperometry is a simple and widely used electrochemical detection technique. Its working principle is: a step potential is applied between the working electrode and the reference electrode of the electrochemical system as an excitation, and the time-varying response current generated by the redox reaction flows through the working electrode and the counter electrode, and the function relationship of the current response and time is measured. However, chronoamperometry is currently only used in electrochemical research, that is, the study of electron transfer kinetics.
[0009] The lithium ion battery stainless steel raw material inspection device of the present invention is a chronoamperometry detection system. Since the voltage of metallic lithium is usually lower than the voltage of stainless steel, the metallic lithium sheet serves as both a reference electrode and a counter electrode and is in contact and electrically connected with the negative electrode shell. Moreover, since the voltage of metallic lithium (3.9V) is substantially consistent with the voltage (3.9V) of the lithium ion battery in the storage state, the storage state of the lithium ion battery can be simulated by using the metallic lithium sheet as a reference electrode. Meanwhile, the stainless steel raw material sheet of the lithium ion battery serves as a working electrode and is in contact and electrically connected with the positive electrode shell. In addition, the metallic lithium sheet, the stainless steel raw material sheet of the lithium ion battery to be tested, and the lithium ion electrolyte to be tested are sealed together in the sealed shell through a sealed shell to ensure that moisture in the air will not contaminate the lithium ion electrolyte. Then, the inspection device is placed in an electrochemical workstation and the chronoamperometry detection system of the electrochemical workstation is started for detection. The chronoamperometry detection system of the electrochemical workstation is used for detection. The current method detection system can directly measure and give a functional relationship curve of current and time. By observing whether the current value fluctuates with the increase of time, it is judged whether the stainless steel raw material sheet to be tested in the inspection device is corroded, thereby realizing a quick and intuitive judgment of the compatibility between the stainless steel raw material of the lithium ion battery to be tested and the electrolyte for the lithium ion battery to be tested under normal storage conditions; in addition, the positive and negative electrode shells are both selected from the positive and negative electrode shells of the same material as the stainless steel raw material sheet of the lithium ion battery, so as to avoid the current test results generated between two different stainless steel products and the electrolyte being inconsistent and confusing when the materials of the electrode shell and the stainless steel raw material sheet of the lithium ion battery are different, thereby affecting the accuracy of the test results; the device of the present invention is a two-electrode system with a simple structure, easy operation, good airtightness, and a more intuitive test result of the chronoamperometry method, which can realize the purpose of quickly judging the compatibility between the stainless steel raw material and the electrolyte.
[0010] Preferably, the sealed shell is provided with a conductive column, a stainless steel raw material sheet of the lithium-ion battery to be tested, a diaphragm and a metal lithium sheet stacked in sequence from top to bottom, the upper surface of the conductive column is in contact and electrically connected with the inner bottom surface of the positive electrode shell, and the lower surface of the metal lithium sheet is in contact and electrically connected with the inner bottom surface of the negative electrode shell, and the conductive column meets at least one of the following two conditions: (1) the conductive column is made of a material that does not chemically react with the electrolyte of the lithium-ion battery to be tested; (2) the conductive column is made of the same material as the stainless steel raw material sheet of the lithium-ion battery to be tested. The conductive column plays a conductive role between the stainless steel raw material sheet of the lithium-ion battery and the positive electrode shell, and at the same time, when the thickness of the stainless steel raw material sheet of the lithium-ion battery is thin, it plays a role in making the metal lithium sheet, the diaphragm and the stainless steel sheet contact more closely; in order to avoid the conductive column and the electrolyte from chemically reacting to affect the test results, the conductive column needs to be made of a material that does not chemically react with the electrolyte or a conductive column made of the same material as the stainless steel raw material sheet of the lithium-ion battery. The conductive column is preferably a hard conductive column, which can make the metal lithium, the diaphragm and the stainless steel sheet contact more closely. Furthermore, the conductive column is preferably a cylindrical structure wound by aluminum foil, which is the same material as the battery tab, and no additional materials need to be purchased.
[0011] The second object of the present invention is to provide a method for inspecting stainless steel raw materials for lithium ion batteries, which comprises the following steps: first assembling the above-mentioned stainless steel raw material inspection device for lithium ion batteries; then placing the inspection device in an electrochemical workstation, wherein the positive and negative electrodes of the electrochemical workstation are electrically connected to the outer bottom surfaces of the positive and negative electrode shells of the inspection device respectively; finally, starting the chronoamperometry program on the electrochemical workstation to detect the inspection device, and the display of the electrochemical workstation will display a curve of the change of current over time. When the current fluctuates with the increase of time, the stainless steel raw material for the lithium ion battery is corroded, and the stainless steel raw material for the lithium ion battery to be tested is not compatible with the electrolyte for the lithium ion battery to be tested; when the current does not fluctuate with the increase of time, the stainless steel raw material for the lithium ion battery is not corroded, and the stainless steel raw material for the lithium ion battery to be tested is compatible with the electrolyte for the lithium ion battery to be tested. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is an axial cross-sectional structural diagram of a lithium-ion battery stainless steel raw material inspection device of any one of Examples 1 to 4;
[0013] Figure 2 This is a current-time variation curve diagram of the lithium-ion battery stainless steel raw material inspection device of Example 1 measured by the chronoamperometry;
[0014] Figure 3 This is a microscope image of a stainless steel raw material sheet in the lithium-ion battery stainless steel raw material inspection device of Example 1 after being tested by chronoamperometry;
[0015] Figure 4 This is a current-time variation curve diagram of the lithium-ion battery stainless steel raw material inspection device of Example 2 measured by the chronoamperometry;
[0016] Figure 5 This is a microscope image of a stainless steel raw material sheet in the lithium-ion battery stainless steel raw material inspection device of Example 2 after being tested by chronoamperometry;
[0017] Figure 6 The current-time variation curves of the lithium ion battery stainless steel raw material inspection device of Examples 3 and 4 measured by the chronoamperometry;
[0018] Figure 7 This is a microscope image of a stainless steel raw material sheet in the lithium-ion battery stainless steel raw material inspection device of Example 3 after being tested by chronoamperometry;
[0019] Figure 8 This is a microscope image of a stainless steel raw material sheet in the lithium-ion battery stainless steel raw material inspection device of Example 4 after being tested by chronoamperometry;
[0020] Fig. 9 This is an axial cross-sectional structural diagram of a lithium-ion battery stainless steel raw material inspection device according to Example 5;
[0021] Fig.10 It is a top view of the conductive column. DETAILED DESCRIPTION
[0022] Now 5 embodiments of the present invention are specifically described:
[0023] Example 1
[0024] like Figure 1As shown, a lithium ion battery stainless steel raw material inspection device comprises a sealed shell 1, the sealed shell 1 is composed of a positive electrode shell 11, a negative electrode shell 12 and a sealing ring 13, wherein the positive electrode shell 11 and the negative electrode shell 12 are both cylindrical, the positive electrode shell 11 is only opened at the lower end, and the negative electrode shell 12 is only opened at the upper end, the positive and negative electrode shells (11, 12) are buckled up and down, and a gap is left between the positive and negative electrode shells (11, 12), and the sealing ring 13 is filled in the gap to achieve sealing and insulation between the positive and negative electrode shells (11, 12); the sealed shell 1 is stacked from bottom to top with a metal lithium sheet 2, a diaphragm 3, a lithium ion battery stainless steel raw material sheet 4 to be tested and a conductive column 6; the conductive column 6 is made of a material that does not chemically react with the lithium ion battery electrolyte 5 to be tested; The diaphragm 3 completely covers the metal lithium sheet 2 and the lithium-ion battery stainless steel raw material sheet 4, so that the diaphragm 3 completely separates the metal lithium sheet 2 from the lithium-ion battery stainless steel raw material sheet 4; the conductive column 6 is in contact and electrically connected with the inner bottom surface of the positive electrode shell 11, and the metal lithium sheet 2 is in contact and electrically connected with the inner bottom surface of the negative electrode shell 12; the inner cavity of the cylinder of the sealing shell 1 encapsulates the lithium-ion battery electrolyte 5 to be tested, and the lithium-ion battery stainless steel raw material sheet 4, the diaphragm 3 and the metal lithium sheet 2 are all immersed in the electrolyte 5; the positive and negative electrode shells (11, 12) are both selected from the same positive and negative electrode shells as the lithium-ion battery stainless steel raw material sheet 4; when working, the inspection device is placed in an electrochemical workstation (existing common structure, not shown) and the chronoamperometry program of the electrochemical workstation is started for detection;
[0025] Wherein, the lithium-ion battery stainless steel raw material sheet 4 to be tested is a 304 stainless steel sheet, and the lithium-ion battery electrolyte 5 to be tested is a K01 electrolyte.
[0026] A lithium ion battery stainless steel raw material inspection method comprises the following steps: first assembling the above-mentioned lithium ion battery stainless steel raw material inspection device; then placing the inspection device in an electrochemical workstation, wherein the positive and negative electrodes of the electrochemical workstation are electrically connected to the outer bottom surfaces of the positive and negative electrode shells of the inspection device respectively; finally, starting the chronoamperometry program on the electrochemical workstation to detect the inspection device, and the display of the electrochemical workstation will display a curve of the change of current over time. When the current fluctuates with the increase of time, the lithium ion battery stainless steel raw material is corroded, and the lithium ion battery stainless steel raw material to be tested is not compatible with the lithium ion battery electrolyte to be tested; when the current does not fluctuate with the increase of time, the lithium ion battery stainless steel raw material is not corroded, and the lithium ion battery stainless steel raw material to be tested is compatible with the lithium ion battery electrolyte to be tested.
[0027] The test results of the lithium ion battery stainless steel raw material inspection device of Example 1 after being placed in an electrochemical workstation for chronoamperometry test at room temperature are as follows: Figure 2 As shown, observe Figure 2 From the current-time curve, we can see that as time goes by, the current continues to decrease and fluctuates, indicating that when 304 stainless steel is used as the stainless steel raw material for lithium-ion batteries (for making the pole shell) and K01 electrolyte is used as the electrolyte for lithium-ion batteries to assemble lithium-ion batteries, corrosion reaction will occur when the stainless steel pole shell contacts the electrolyte under normal temperature conditions.
[0028] At the same time, the applicant disassembled the test device after the chronoamperometry test and observed the surface of the lithium-ion battery stainless steel raw material sheet 4 to be tested inside the battery through a microscope. The observation results are as follows: Figure 3 As shown, in Figure 3 It can be clearly seen that there are indeed many corrosion spots on the surface of the lithium-ion battery stainless steel raw material sheet 4 to be tested.
[0029] Therefore, 304 stainless steel raw materials are not compatible with K01 electrolyte at room temperature.
[0030] Example 2
[0031] The lithium ion battery stainless steel raw material inspection device and inspection method of Example 2 are different from those of the example in that the lithium ion battery stainless steel raw material sheet 4 to be tested is a 316L stainless steel sheet, and the lithium ion battery electrolyte 5 to be tested is a K01 electrolyte.
[0032] The test results of the lithium ion battery stainless steel raw material inspection device of Example 2 after being placed in an electrochemical workstation for chronoamperometry test at room temperature are as follows: Figure 4 As shown, observe Figure 4 From the current-time curve, we can see that the current does not fluctuate as time increases, indicating that when 316L stainless steel is used as the stainless steel raw material for lithium-ion batteries (for making the pole shell) and K01 electrolyte is used as the electrolyte for lithium-ion batteries to assemble lithium-ion batteries, under normal temperature conditions, no corrosion reaction occurs when the stainless steel pole shell contacts the electrolyte.
[0033] At the same time, the applicant disassembled the test device after the chronoamperometry test and observed the surface of the lithium-ion battery stainless steel raw material sheet 4 to be tested inside the battery through a microscope. The observation results are as follows: Figure 5 As shown, in Figure 3 It can be clearly seen that no corrosion spots appear on the surface of the lithium-ion battery stainless steel raw material sheet 4 to be tested.
[0034] Therefore, 316L stainless steel raw material is compatible with K01 electrolyte at room temperature.
[0035] Example 3
[0036] The lithium ion battery stainless steel raw material inspection device and inspection method of Example 3 are different from those of the examples in that the lithium ion battery stainless steel raw material sheet 4 to be tested is a 304 stainless steel sheet, and the lithium ion battery electrolyte 5 to be tested is an E2656 electrolyte.
[0037] The test results of the lithium ion battery stainless steel raw material inspection device of Example 3 after being placed in an electrochemical workstation at 45°C and subjected to a chronoamperometric test are as follows: Figure 6 As shown, observe Figure 6 From the current-time curve corresponding to "45℃-304", it can be seen that the current fluctuates significantly with the increase of time, indicating that when 304 stainless steel is used as the stainless steel raw material of lithium-ion batteries (for making the pole shell) and E2656 electrolyte is used as the electrolyte for lithium-ion batteries to assemble lithium-ion batteries, corrosion reaction will occur when the stainless steel pole shell contacts the electrolyte at 45℃.
[0038] At the same time, the applicant disassembled the test device after the chronoamperometry test and observed the surface of the lithium-ion battery stainless steel raw material sheet 4 to be tested inside the battery through a microscope. The observation results are as follows: Figure 7 As shown, in Figure 3 It can be clearly seen that many corrosion spots appear on the surface of the lithium-ion battery stainless steel raw material sheet 4 to be tested.
[0039] Therefore, 304 stainless steel raw materials are not compatible with E2656 electrolyte at 45°C.
[0040] Example 4
[0041] The lithium ion battery stainless steel raw material inspection device and inspection method of Example 4 are different from those of the examples in that the lithium ion battery stainless steel raw material sheet 4 to be tested is a 316L stainless steel sheet, and the lithium ion battery electrolyte 5 to be tested is an E2656 electrolyte.
[0042] The test results of the lithium ion battery stainless steel raw material inspection device of Example 4 after being placed in an electrochemical workstation at 45°C and subjected to a chronoamperometric test are as follows: Figure 6 As shown, observe Figure 6 From the current-time curve corresponding to "45℃-316", it can be seen that the current does not fluctuate with time, indicating that when 316L stainless steel is used as the stainless steel raw material for lithium-ion batteries (for making the pole shell) and E2656 electrolyte is used as the electrolyte for lithium-ion batteries to assemble lithium-ion batteries, no corrosion reaction occurs when the stainless steel pole shell contacts the electrolyte at 45℃.
[0043] At the same time, the applicant disassembled the test device after the chronoamperometry test and observed the surface of the lithium-ion battery stainless steel raw material sheet 4 to be tested inside the battery through a microscope. The observation results are as follows: Figure 8 As shown, in Figure 8 It can be observed that no corrosion spots appear on the surface of the lithium-ion battery stainless steel raw material sheet 4 to be tested.
[0044] Therefore, 316L stainless steel raw material is compatible with E2656 electrolyte at 45°C.
[0045] In the lithium-ion battery stainless steel raw material inspection devices in the above-mentioned embodiments 1 to 4, the sealed housing 1 is provided with a conductive column 6, and the conductive column 6 is in contact with and electrically connected to the inner bottom surface of the positive electrode shell 11. However, in fact, the sealed housing 1 of the present invention may not be provided with a conductive column 6, and when the lithium-ion battery stainless steel raw material sheet 4 to be tested is thick enough, so that the total thickness of the metal lithium sheet 2, the diaphragm 3, and the lithium-ion battery stainless steel raw material sheet 4 to be tested is equivalent to the inner cavity height of the sealed housing 1, the conductive column 6 may not be provided. The inventor also conducted an experiment without providing the conductive column 6 (i.e., embodiment 5).
[0046] Example 5
[0047] The lithium ion battery stainless steel raw material inspection device and inspection method of Example 5 are different from those of Example 2 in that: a metal lithium sheet 2, a diaphragm 3 and a lithium ion battery stainless steel raw material sheet 4 to be tested are stacked in sequence from bottom to top in the sealed shell 1; the lithium ion battery stainless steel raw material sheet 4 is in contact and electrically connected with the inner bottom surface of the positive electrode shell 11.
[0048] The test result of the lithium-ion battery stainless steel raw material inspection device of Example 5 after being placed in an electrochemical workstation at room temperature and subjected to a chronoamperometry test is: the current does not fluctuate as time increases, which is consistent with the test result of Example 2.
[0049] The K01 electrolyte and E2656 electrolyte used in Examples 1 to 3 are both commercially available products, wherein the E2656 electrolyte was purchased from Guangzhou Tianci High-tech Materials Co., Ltd., and the K01 electrolyte was purchased from Jiangxi Kedeyi New Energy Materials Technology Co., Ltd.
[0050] In Examples 1 to 5, the conductive column 6 is a cylindrical structure formed by winding aluminum foil. Aluminum does not chemically react with the electrolyte 5 for lithium-ion batteries. However, the conductive column 6 of the present invention is not limited to a cylindrical structure formed by winding aluminum foil, and it can also be a cylindrical aluminum ingot or other conductive column that does not chemically react with the electrolyte except aluminum. Of course, the conductive column of the present invention can also be a conductive column made of the same material as the stainless steel raw material sheet 4 of the lithium-ion battery to be tested.
[0051] The lithium ion battery stainless steel raw material inspection device of the present invention is a chronoamperometry detection system. Since the voltage of metallic lithium is usually lower than the voltage of stainless steel, the metallic lithium sheet 2 serves as both a reference electrode and a counter electrode and is in contact and electrically connected with the negative electrode shell 12. Moreover, since the voltage of metallic lithium (3.9V) is substantially consistent with the voltage (3.9V) of the lithium ion battery in the storage state, the storage state of the lithium ion battery can be simulated by using the metallic lithium sheet 2 as a reference electrode. Meanwhile, the lithium ion battery stainless steel raw material sheet 4 to be tested serves as a working electrode and is in contact and electrically connected with the positive electrode shell 11. In addition, the metallic lithium sheet 2, the lithium ion battery stainless steel raw material sheet 4, and the lithium ion electrolyte 5 are sealed together in the sealed shell 1 through the sealed shell 1 to ensure that moisture in the air will not contaminate the lithium ion electrolyte. Then, the inspection device is placed in an electrochemical workstation and the chronoamperometry detection system of the electrochemical workstation is started for detection. The chronoamperometry detection system can directly measure and give a functional relationship curve of current and time, and judge whether the stainless steel raw material sheet in the inspection device is corroded by observing whether the current value fluctuates with the increase of time, thereby realizing a quick and intuitive judgment on the compatibility between the stainless steel raw material of the lithium ion battery and the electrolyte under normal storage conditions; in addition, the positive and negative electrode shells (11, 12) are both selected from the same positive and negative electrode shells as the lithium ion battery stainless steel raw material sheet 4 to be tested, so as to avoid that when the materials of the electrode shell and the lithium ion battery stainless steel raw material sheet 4 are different, the current test results generated between two different stainless steel products and the lithium ion electrolyte 5 to be tested are inconsistent, confused with each other, and affect the accuracy of the test results; the device of the present invention is a two-electrode system, with a simple structure, easy to operate, good airtightness, and the test results of the chronoamperometry are more intuitive, which can realize the purpose of quickly judging the compatibility between the stainless steel raw material and the electrolyte.
[0052] The lithium-ion battery stainless steel raw material inspection device and inspection method of embodiments 1 to 4 of the present invention can be improved as follows: the conductive column 6 is preferably a hard conductive column, which can make the metal lithium sheet 2, the diaphragm 3, and the stainless steel raw material sheet 4 contact more closely.
Claims
1. A lithium-ion battery stainless steel raw material inspection device, characterized in that: The invention comprises a sealed shell, wherein the sealed shell is composed of a positive electrode shell, a negative electrode shell and a sealing ring, wherein the positive electrode shell and the negative electrode shell are both cylindrical, the positive electrode shell is only opened at the lower end, and the negative electrode shell is only opened at the upper end, the positive and negative electrode shells are buckled up and down, and a gap is left between the positive and negative electrode shells, and the sealing ring is filled in the gap to achieve sealing and insulation between the positive and negative electrode shells; the sealed shell is stacked with conductive columns, stainless steel raw material sheets of lithium ion batteries to be tested, diaphragms and metal lithium sheets in sequence from top to bottom; the diaphragms completely cover the metal lithium sheets and the stainless steel raw materials of lithium ion batteries The material sheet is set; the upper surface of the conductive column is in contact and electrically connected with the inner bottom surface of the positive electrode shell, the lower surface of the metal lithium sheet is in contact and electrically connected with the inner bottom surface of the negative electrode shell, the inner cavity of the cylinder of the sealed shell is encapsulated with an electrolyte for the lithium ion battery to be tested, and the lithium ion battery stainless steel raw material sheet, the diaphragm and the metal lithium sheet are all immersed in the electrolyte; the positive and negative electrode shells are both made of the same material as the lithium ion battery stainless steel raw material sheet; when working, the inspection device is placed in an electrochemical workstation and the chronoamperometry program of the electrochemical workstation is started for detection; The conductive column meets at least one of the following two conditions: (1) the conductive column is made of a material that does not chemically react with the electrolyte of the lithium-ion battery to be tested; (2) the conductive column is made of the same material as the stainless steel raw material sheet of the lithium-ion battery to be tested.
2. A lithium-ion battery stainless steel raw material inspection device according to claim 1, characterized in that: The conductive column is a hard conductive column.
3. The lithium-ion battery stainless steel raw material inspection device according to claim 1, characterized in that: The conductive column is a cylindrical structure formed by winding aluminum foil.
4. A method for inspecting stainless steel raw materials for lithium-ion batteries, characterized in that: The invention comprises the following steps: firstly assembling the lithium ion battery stainless steel raw material inspection device as described in any one of claims 1 to 3; then placing the inspection device in an electrochemical workstation, wherein the positive and negative electrodes of the electrochemical workstation are electrically connected to the outer bottom surfaces of the positive and negative electrode shells of the inspection device respectively; finally, starting the chronoamperometry program on the electrochemical workstation to detect the inspection device, and the display of the electrochemical workstation will display the curve of the current changing with time. When the current fluctuates with the increase of time, the lithium ion battery stainless steel raw material is corroded, and the lithium ion battery stainless steel raw material to be tested is not compatible with the lithium ion battery electrolyte to be tested; when the current does not fluctuate with the increase of time, the lithium ion battery stainless steel raw material is not corroded, and the lithium ion battery stainless steel raw material to be tested is compatible with the lithium ion battery electrolyte to be tested.
Citation Information
Patent Citations
Method for detecting shell stability of lithium ion battery
CN102937615A
In-situ synchronous observation system for electrode reaction of lithium ion battery
CN110261380A
Lithium ion battery stainless steel raw material inspection device
CN214374474U